Podocalyxin‐like protein 1 is a relevant marker for human c‐kitpos cardiac stem cells. (30th July 2013) - Moscoso, Isabel; Tejados, Naiara; Barreiro, Olga; Sepúlveda, Pilar; Izarra, Alberto; Calvo, Enrique; Dorronsoro, Akaitz; Salcedo, Juan Manuel; Sádaba, Rafael; Díez‐Juan, Antonio; Trigueros, César; Bernad, Antonio
Abstract: Cardiac progenitor cells (CPCs) from adult myocardium offer an alternative cell therapy approach for ischaemic heart disease. Improved clinical performance of CPCs in clinical trials requires a comprehensive definition of their biology and specific interactions with the environment. In this work we characterize specific human CPC surface markers and study some of their related functions. c‐kit pos human CPCs (hCPCs) were characterized for cell surface marker expression, pluripotency, early and late cardiac differentiation markers and therapeutic activity in a rat model of acute myocardial infarction. The results indicate that hCPCs are a mesenchymal stem cell (MSC)‐like population, with a similar immunoregulatory capacity. A partial hCPC membrane proteome was analysed by liquid chromatography–mass spectrometry/mass spectrometry and 36 proteins were identified. Several, including CD26, myoferlin and podocalyxin‐like protein 1 (PODXL), have been previously described in other stem‐cell systems. Suppression and overexpression analysis demonstrated that PODXL regulates hCPC activation, migration and differentiation; it also modulates their local immunoregulatory capacity. Therefore, hCPCs are a resident cardiac population that shares many features with hMSCs, including their capacity for local immunoregulation. Expression of PODXL appears to favour the immature state of hCPCs, while its downregulation facilitates their differentiation. Copyright © 2016 John Wiley & Sons, Ltd.